The Influence of Gender, Age, Academic Level and Motivation on Satisfaction Toward Benefits Received by Gig Economy Workers in Malaysia - Norwani, Norlia Mat; Ismail, Zuriadah; Nasir, Nur Nastasya Athira Mohd; Yusof, Rohaila; Jamaluddin, Nur Sa’adah (Archives of Business Research, 2022)
The emergence of new modes of employment relations has contributed to the development of gig economy workers who are employed on a mostly freelance basis, carrying out short-term jobs or contracts without or with one or more employers. The research aims to identify the level of motivation and satisfaction towards the benefits received by gig economy workers, to assess differences in the level of motivation and satisfaction based on gender, age and academic level and to ascertain if the demographic variables and motivation are predictors of satisfaction. A set of questionnaires in google form is utilized for data collection in the Selangor area via various social media. A total of 384 responses were recorded and analyses including descriptive and inferential tests were done. Both motivation and satisfaction are at a high level. ANOVA tests showed that motivation and satisfaction are significantly different based on gender (motivation: F=6.482, p<0.05 and satisfaction: F=0.040, p<0.05) and age (motivation: F=5.977, p<0.05 and satisfaction: F=3.940, p<0.05). Regression analysis indicated that age and motivation explained 59.0% of the variance in satisfaction (adjusted R2=0.59, F(2,381)=276.020, p<0.05). Policies and interventions can be developed to create an environment and conditions conducive to employee happiness, resulting in an increase in employee motivation and work satisfaction. Because gig workers have demonstrated a desire to learn and grow, respective agencies can provide complimentary, voluntary educational activities such as full-fledged courses and seminars in areas deemed needed.